Animosity and Tourism: Resident Perspectives - Farmaki, Anna (My University, 2023)
Despite the growing interest that scholars have paid to animosity in tourism settings, pertinent research draws mostly from tourist perspectives to examine the effects of animosity on travel-related decision-making. The aim of this study is to explore the animosity perceptions of residents against Russian tourists who, following the Russia-Ukraine conflict and the sanctions imposed on Russia, are likely to experience intense animosity when traveling abroad. The study draws from interviews with residents based in Cyprus, a well-known island destination in the Mediterranean that is popular among Russian tourists. The study concludes that animosity within tourism settings represents a complex construct as it evolves and manifests varyingly, depending on multiple factors including media representations, passage of time from occurrence of event, previously held attitudes toward tourists, political or cultural affinity and subjective norms. The study offers a classification of resident animosity/affinity which provides theoretical and practical insights.
Keywords: animosity; residents; Russian tourists; tourism; Ukrainian crisis